P423 Azathioprine still remains the first step-up therapy in patients with Inflammatory Bowel Disease in low-middle income countries. (21st January 2022) - Ranjan, M K; Kumar, P; Vuyyuru, S K; Kante, B; Sahu, P; Mundhra, S; Golla, R; Singh, M; Virmani, S; Sharma, R; Panwar, R; Das, P; et al.
Abstract: Background: Inflammatory bowel disease (IBD) including Ulcerative Colitis (UC) and Crohn's Disease (CD) is characterized by remitting/relapsing course. A proportion of patients with UC, and almost all patients with CD require long-term immunosuppression to maintain endoscopic and clinical remission and prevent disease progression. The present study aimed to evaluate the long-term efficacy of thiopurines, their predictors, and the effect of the early use of thiopurines on disease outcomes in patients with IBD. Methods: A retrospective cohort analysis of patients with IBD following up in IBD clinic at AIIMS, New Delhi, India from, 2004–2020. Efficacy was defined as a state of not requiring hospitalization, anti-TNF agents, surgery, and only minimum (≤, 1 steroid course in, 2 years) steroid requirement during follow-up. Early and late thiopurine initiation was defined as commencement of thiopurines ≤2 and >2 years of disease onset, respectively. Results: Of, 1264 consecutive patients on thiopurines (both, 6-MP and azathioprine), 988 (UC:720, CD:268) were considered for efficacy analysis (males-60.8%, mean age at disease onset-31.69±12.34 years and thiopurine initiation-35±13.14 years). Time to event analysis showed a median efficacy rate of, 79%, 72% and, 68%, 61% at, 5 and, 10 years in UC and CD patients respectively after thiopurine initiation. On multivariate analysis, only the male sex was found to be a significant predictor of relapse (HR:, 1.49, 95% CI:, 1.021–2.194; P=0.039) in UC and Ileal involvement (HR:, 0.391, 95% CI:, 0.176–0.86; P=, 0.021) and steroid-dependent disease (HR:, 0.429, 95% CI:, 0.186–0.965; P=, 0.041) were associated with decreased risk of relapse and presence of any adverse event was associated with increased risk of relapse (HR:, 2.37, 95%CI:, 1.39–4.05; P=0.008). Kaplan Meier survival analysis showed no difference between the efficacy of early and late thiopurine groups, both in UC (Log-rank test P = 0.72) and CD (Log-rank test P = 0.76). Figure, 1: Kaplan Meier curve showing relapse-free survival on thiopurine in ulcerative colitis and Crohn's disease. Figure, 2: Kaplan Meier survival analysis comparing relapse-free survival in early vs late thiopurine initiation group in UC (Log-rank test P = 0.72). Figure, 3: Kaplan Meier survival analysis comparing relapse-free survival in early vs late thiopurine initiation group in CD (Log-rank test P-value:, 0.764). Conclusion: Thiopurines still remains a viable long-term option for maintenance of remission in patients with IBD, especially in resource-limited countries. Their use can be further enhanced by optimizing their therapy and regular monitoring for adverse events.